Pharmacokinetics of fluconazole in cerebrospinal fluid and serum of rabbits: validation of an animal model used to measure drug concentrations in cerebrospinal fluid. - Madu, A (1994)
Complete concentration-time data describing the pharmacokinetics of fluconazole in the cerebrospinal fluid (CSF) following a single dose are not available for humans or animals. We studied the pharmacokinetics of fluconazole with an indwelling intracisternal needle as described by R.G. Dacey and M.A. Sande (Antimicrob. Agents Chemother. 6:437-441, 1974). To determine whether the presence of an intracisternal needle alters pharmacokinetics in the CSF, we validated this model with uninfected rabbits by measuring pharmacokinetic constants following direct intracisternal and intravenous administration of fluconazole. Following direct injection, there was no alteration of elimination rates in the CSF with increasing sample number or time. Following intravenous administration, the penetration and kinetic constants were the same in individual animals from which multiple CSF samples were obtained as in a composite subject constructed by pooling virgin samples from different animals. The presence of the intracisternal needle did not alter CSF chemistry or leukocyte counts, and erythrocyte contamination was < 0.001%. While drug concentrations were measured by a microbiological assay, we also compared the sensitivity and reproducibility of a high-performance liquid chromatography (HPLC) assay with those of the microbiological assay. Following a single intravenous dose, the maximum concentration of the drug in serum, the time to maximum concentration of the drug in serum, the terminal elimination half-life in the CSF, and the percent penetration by fluconazole were 6.12 micrograms/ml, 1 h, 9.0 h, and 84.3%, respectively. We conclude that the sampling of CSF via an indwelling needle does not alter fluconazole pharmacokinetics, cause inflammation, or alter chemical parameters; that the microbiological assay is at least equivalent in sensitivity and reproducibility to the HPLC assay; and that robust parameters describing the pharmacokinetics of fluconazole are possible with this model.